基于NDVI的乌兰布和沙漠养牛生态与经济效益研究 [Study on the ecological effects of dairy cow farming in Ulan Buh desert] - Wu, Xindi; Bai, Keyu (2022)
Using remote sensing, this study focuses on dairy cow farming model developing on the desert in Dengkou county of Inner Mongolia, analyzes the dynamic changes of the number of dairy cows in this area from 2005 to 2021. Based on the analysis of the NDVI using MODIS dataset of remote sensing, the result shows that with dairy cow farming industry developing, the local vegetation coverage has changed significantly, increasing from 21.85% in 2005 to 37.31% in 2021. Further correlation analysis shows that the positive correlation between the number of dairy cows and vegetation coverage, with correlation coefficient of 0.87. and desert dairy cow farming developing has positive correlation with the local GDP with a correlation coefficient of 0.69. In conclusion, it is a win-win model for developing the desert dairy cow farming to improve the ecological environment and benefit the local livelihood.